Study on dynamic model and dynamic characteristics of Delingha 50 MW trough solar field. (October 2022) - Lengge, Si; Ershu, Xu; Jianfang, Tang; Jun, Dong; Dongming, Zhao; Hui, Xu; Yanan, Zhang; Gang, Yu; Hongjuan, Hou
Highlights: Hydrodynamic calculation model and heat transfer dynamic model are developed. The full-condition simulation of the 50 MW trough solar field is realized. The built model is validated with actual operation data. The DNI, oil flow, and inlet temperature disturbance simulations are carried out and analyzed. The dynamic response curves and the inertia time constant under disturbance are obtained. Abstract: China General Nuclear Power Group (CGNPC) Delingha 50 MW parabolic trough solar thermal power plant is the first commercial trough solar plant in China, and its solar field consists of 190 parallel heat collecting loops. For large-scale trough solar plant, balancing the flow rate of heat absorbing medium in each loop and stabilizing the outlet temperature are the key technologies and difficult problems. Regarding the Delingha 50 MW solar field as the research object, this paper mainly focusing on the dynamic characteristics of flow and heat transfer in the solar field. The hydrodynamic calculation model and the heat transfer dynamic model are established on the real-time dynamic simulation platform STAR-90. With the actual operation data, the built solar field model is validated by comparing the simulation results. On this basis, the disturbance simulations of direct normal irradiance (DNI), heat transfer oil's mass flow and heat transfer oil's inlet temperature are carried out. The dynamic response curves of disturbance and the thermal inertia time constant of the loops are obtained. The conclusions lay a theoretical foundation for the formulation of outlet medium's temperature control strategy in the solar field of large-scale trough solar thermal power generation system.